Multiple roles of neuronal extracellular vesicles in neurological disorders - Jiao, Zhigang; He, Zhengyi; Liu, Nanhai; Lai, Yanwei; Zhong, Tianyu (Frontiers in Cellular Neuroscience, 2022)
Neuropathy is a growing public health problem in the aging, adolescent, and sport-playing populations, and the number of individuals at risk of neuropathy is growing; its risks include aging, violence, and conflicts between players. The signal pathways underlying neuronal aging and damage remain incompletely understood and evidence-based treatment for patients with neuropathy is insufficiently delivered; these are two of the reasons that explain why neuropathy is still not completely curable and why the progression of the disease cannot be inhibited. Extracellular vesicles (EVs) shuttling is an important pathway in disease progression. Previous studies have focused on the EVs of cells that support and protect neurons, such as astrocytes and microglia. This review aims to address the role of neuronal EVs by delineating updated mechanisms of neuronal damage and summarizing recent findings on the function of neuronal EVs. Challenges and obstacles in isolating and analyzing neuronal EVs are discussed, with an emphasis on neuron as research object and modification of EVs on translational medicine.